2002
DOI: 10.1097/00004647-200210000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Protects Cultured Rat Hippocampal Neurons Against Hypoxic Injury via an Antiexcitotoxic, Caspase-Independent Mechanism

Abstract: The authors investigated the effect of vascular endothelial growth factor (VEGF) on hypoxic injury of cultured rat hippocampal neurons. Treatment with glutamate receptor antagonists prevented hypoxic neuron death. The same magnitude of protection was observed in cultures treated with VEGF, which also reduced excitotoxic neuron death induced directly by an exposure to -methyl-d-aspartate. Vascular endothelial growth factor did not alter the activation of the transcription factor nuclear factor-kappaB during hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 28 publications
5
69
1
Order By: Relevance
“…VEGF-A also protects stressed neurons in culture, for example after serum withdrawal (Jin et al, 2000a), hypoxia (e.g. Jin et al, 2000b;Svensson et al, 2002), mechanical trauma , chemical toxicity (Cui et al, 2011), or excitotoxicity caused by glutamate or the glutamate mimetic AMPA (Bogaert et al, 2010;Matsuzaki et al, 2001;Svensson et al, 2002). As these culture models did not contain blood vessels, it was concluded that the neuronal survival effects of VEGF-A were vessel independent.…”
Section: Vegf-a As a Survival Factor For Developing And Adult Neuronsmentioning
confidence: 99%
“…VEGF-A also protects stressed neurons in culture, for example after serum withdrawal (Jin et al, 2000a), hypoxia (e.g. Jin et al, 2000b;Svensson et al, 2002), mechanical trauma , chemical toxicity (Cui et al, 2011), or excitotoxicity caused by glutamate or the glutamate mimetic AMPA (Bogaert et al, 2010;Matsuzaki et al, 2001;Svensson et al, 2002). As these culture models did not contain blood vessels, it was concluded that the neuronal survival effects of VEGF-A were vessel independent.…”
Section: Vegf-a As a Survival Factor For Developing And Adult Neuronsmentioning
confidence: 99%
“…VEGF enhances neuronal proliferation (Jin et al, 2002;Zhu et al, 2003), neurite outgrowth and maturation (Rosenstein et al, 2003;Khaibullina et al, 2004), and neuronal survival (Jin et al, 2000(Jin et al, , 2001Svensson et al, 2002). A neuroprotective role for VEGF is supported by the demonstration that VEGF reduces excitotoxic damage to cultured hippocampal neurons (Jin et al, 2000;Matsuzaki et al, 2001;Svensson et al, 2002) and reduces damage in vivo after ischemia (Hayashi et al, 1998;Sun et al, 2003) (but see van Bruggen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A modern area of research dealing with VEGF as a means of vascular protection and regeneration aims at neuroprotection; VEGF has been reported to protect motor neurons in vitro from hypoxia-induced toxicity, reactive oxygen and other degrading factors 19 . In addition, VEGF seems to be able to stimulate growth and development of neuronal stem cells as well as to recruit neuronal progenitor cells 20 .…”
Section: Discussionmentioning
confidence: 99%